2019
DOI: 10.1101/633594
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AP-1 Imprints a Reversible Transcriptional Program of Senescent Cells

Abstract: Senescent cells play important physiological-and pathophysiological roles in tumor suppression, tissue regeneration, and aging. While select genetic and epigenetic elements crucial for senescence induction were identified, the dynamics, underlying epigenetic mechanisms, and regulatory networks defining senescence competence, induction and maintenance remain poorly understood, precluding a deliberate therapeutic manipulation of these dynamic processes. Here, we show, using dynamic analyses of transcriptome and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 84 publications
4
10
0
Order By: Relevance
“…It is not fully understood how enhancer chromatin, epigenetic marks, transcription factor recruitment, and the organizational principles of transcription factor networks drive the senescence program. Recent studies showed that the senescence program is predominantly encoded at the enhancer level [66,67] and that the enhancer landscape is dynamically reshaped at each step of the senescence transition [68]. A deeper understanding of the underlying mechanisms might help identify ways in which enhancer regulation could be manipulated to overcome potential SR and endocytosis gene transcriptional silencing in senescent LSECs, which express enhanced levels of heterochromatic marks such as macroH2A and Histone H9Me2 [39].…”
Section: Reversing Transcriptional Silencing Of Srsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not fully understood how enhancer chromatin, epigenetic marks, transcription factor recruitment, and the organizational principles of transcription factor networks drive the senescence program. Recent studies showed that the senescence program is predominantly encoded at the enhancer level [66,67] and that the enhancer landscape is dynamically reshaped at each step of the senescence transition [68]. A deeper understanding of the underlying mechanisms might help identify ways in which enhancer regulation could be manipulated to overcome potential SR and endocytosis gene transcriptional silencing in senescent LSECs, which express enhanced levels of heterochromatic marks such as macroH2A and Histone H9Me2 [39].…”
Section: Reversing Transcriptional Silencing Of Srsmentioning
confidence: 99%
“…This approach represents a broader direction that is not restricted just to reversing transcriptional silencing of SRs but to changes of entire transcriptional network to a younger nonsenescent state. Pioneer transcription factors (that directly bind condensed chromatin) are critical in establishing new cell fate competence: they grant longterm chromatin access to non-pioneer factors and help determine cell identity by opening and licensing the enhancer landscape [68,70,71]. In addition, DNA methylation could play an important role in establishment of senescence as recently was shown for a DNMT1dependent downregulation of BRCA1/ZNF350/RBBP8 repressor complex in the course of oncogene-induced senescence [72].…”
Section: Reprogramming Senescent Lsecsmentioning
confidence: 99%
“…In this study, we pioneered the use of interspecies genetic divergence to screen for components of the senescence regulatory machinery. This strategy complements previous studies of transcription factor binding sites in genes of the senescence program in a single genetic background (17,21). Our approach harnesses the correlation between interspecies variation in sequence and expression levels, as an additional line of evidence for senescence-specific regulatory functions by a given factor.…”
Section: Discussionmentioning
confidence: 83%
“…However, given the complexity of the senescence program, many more regulators likely remain to be identified. Indeed, bioinformatic approaches have identified dozens of other transcription factor candidates in senescence (17)(18)(19)(20)(21)(22)(23)(24), many of which remain unvalidated (but see (18)(19)(20)(21) for recent discoveries of the roles of DLX2, FOXO3 and AP-1 in senescence).…”
Section: Introductionmentioning
confidence: 99%
“…3B). Functional overrepresentation profiling enriched for a highly diverse array of biological processes consistent with a senescence response in the yellow module, including 'p53 pathway, 'Inflammatory response', and 'TGFß signaling', many which overlapped with pathways also activated in senescent human fibroblasts (24,25) (Fig. S4E-F).…”
Section: Senescent Cd8+ T Cells Develop a Unique Gene Expression Signmentioning
confidence: 99%